2012
DOI: 10.1136/bcr-2012-006382
|View full text |Cite
|
Sign up to set email alerts
|

A patient with tuberculous peritonitis with very high serum CA 125: Figure 1

Abstract: An 88-year-old woman presented with abdominal pain and distension. Serum cancer antigen 125 (CA 125) level was very high; however, abdominal CT reveals ascites without definite mass. Ascites analysis revealed a lymphocytic exudate with high adenosine deaminase enzyme level, negative stains for bacteria and negative PCR for Mycobacterium tuberculosis. Presumptive diagnosis for tuberculous peritonitis was made and antituberculous therapy resulted in the resolution of ascites and normalisation of CA 125.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…endometriosis, pancreatitis, peritonitis, IBD) conditions [20]. Notably, increased Ca125 serum levels have been reported in both PTB and pulmonary TB and Ca125 can also be used for monitoring anti-TB treatment response [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…endometriosis, pancreatitis, peritonitis, IBD) conditions [20]. Notably, increased Ca125 serum levels have been reported in both PTB and pulmonary TB and Ca125 can also be used for monitoring anti-TB treatment response [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…4 CA 125 is a soluble glycoprotein oncofetal antigen that was found in coelomic epithelium during fetal development. CA 125 is widely recognized and utilized in monitoring recurrence of epithelial ovarian cancer, treatment responsiveness, and to distinguish malignant from benign pelvic masses.…”
Section: Discussionmentioning
confidence: 99%
“…CA 125 is widely recognized and utilized in monitoring recurrence of epithelial ovarian cancer, treatment responsiveness, and to distinguish malignant from benign pelvic masses. 4,5 For premenopausal women, CA 125 levels are usually elevated with benign gynecologic condition such as fibroid, benign ovarian cysts, and endometriosis. Terada et al published a study stating that menopausal females with an elevated CA 125 and without ovarian cancer are associated with increased risk of premature mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Many reports have reported an association between peritoneal tuberculosis and high serum CA 125. 11,12 In addition, elevated serum CA 125 levels have a high predictive value for a diagnosis of peritoneal tuberculosis, whereas decreased serum CA 125 levels can be used to evaluate the efficacy of therapy in peritoneal tuberculosis. 3,[11][12][13] Some studies reported that while the serum CA 125 levels may be elevated in patients with peritoneal tuberculosis (approximately 10-to 20-fold higher than normal values), they would likely be much higher in patients with peritoneal carcinomatosis (approximately 60-fold higher than normal values).…”
mentioning
confidence: 99%